Management & Organisational Behaviour. - Mullins, Laurie J.; Christy, Gill (Harlow, England : Pearson, 2016)
Presenting a managerial approach to the study of organisational behaviour, with an emphasis on improving working performance through a better understanding of human resources, this book contains summaries, review questions and assignments.
Previous edition: Harlow: Financial Times Prentice Hall, 2010.
Includes bibliographical references and index.
Keywords: Management; Organizational behavior; Business and Management